Evoluç\~ao urbana e espraiamento na Regi\~ao Metropolitana de S\~ao Paulo - Vanessa Gapriotti Nadalin; Danilo Camargo Igliori (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This work deals with the issue of urban sprawl within the context of the S\~ao Paulo Metropolitan Area. We define urban sprawl as leapfrogging, not concentrated and not dense urban growth. We analyze urban area maps between the year of 1962 and 2002, the evolution of population and jobs density and the evolution of density gradients. We propose the construction of a sprawl index. Its evolution is analyzed using Markov chain models, while we search its determinants using econometric tools. Results point out that there was urban sprawl in the most recent period of time. The determinants show the link between this phenomenon and the occupation of suburbs by low income families.
Keywords: R32; 330